1984
DOI: 10.5006/1.3593933
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Emission Characterization of Corrosion Induced Damage in Reinforced Concrete

Abstract: The deterioration of steel reinforced concrete caused by reinforcing bar corrosion is recognized as a major technical problem in the State of Florida and nationwide. This mode of failure is usually recognized in the final stages when surface cracking and spalling of the concrete occurs. The purpose of this study is to extend work previously reported on a nondestructive monitoring technique to detect, characterize, and locate corrosion induced structural damage. Acoustic emission technology is used to monitor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 2 publications
1
22
0
Order By: Relevance
“…Moreover, the control emitted virtually zero emissions over the entire test duration (~120 hours) strongly suggesting that the emissions from Beams 1-3 are as a result of corrosion as opposed to other mechanisms such as thermally induced AE or water loss. The clear distinction between the corroding beams and the control supports Dunn et al [26] who found that AE could distinguish between noble and active specimens.…”
Section: Acoustic Emissionsupporting
confidence: 73%
See 1 more Smart Citation
“…Moreover, the control emitted virtually zero emissions over the entire test duration (~120 hours) strongly suggesting that the emissions from Beams 1-3 are as a result of corrosion as opposed to other mechanisms such as thermally induced AE or water loss. The clear distinction between the corroding beams and the control supports Dunn et al [26] who found that AE could distinguish between noble and active specimens.…”
Section: Acoustic Emissionsupporting
confidence: 73%
“…Li and Shah [23] successfully used AE on concrete under going uniaxial tensile tests, where the cause of emission was the nucleation of microcracks. Whilst AE has been used as a method to monitor the structural integrity of beams placed under increasing loads with various levels of corrosion induced damage [24,25], AE has also been applied to the detection of steel reinforcement corrosion [26][27][28][29].…”
Section: Principles Of Aementioning
confidence: 99%
“…9(b). Comparable behaviour was reported by Dunn et al [12] who considered this a characteristic of periods of crack extension followed by continued corrosion. They believed that once the void provided by a previous crack was filled by new corrosion products, additional cracking then followed.…”
Section: Strengthmentioning
confidence: 57%
“…The number of hits over time is often used in AE analysis [10][11][12][13]18], however, whilst this is often used to assess the rate of activity of a sample over time, the data is non- A summary of the key data is presented in Table 3, listing the total hits, ABS energy, Table 3 as no corrosion products were found. The results hereon in have been divided into three areas to describe the effects of strength, cover depth and rebar diameter.…”
Section: Evidence Of Corrosion and Resulting Aementioning
confidence: 99%
See 1 more Smart Citation